2024
DOI: 10.1242/dmm.050574
|View full text |Cite
|
Sign up to set email alerts
|

ATP1A3 regulates protein synthesis for mitochondrial stability under heat stress

Fumihiko Fujii,
Hikaru Kanemasa,
Sayaka Okuzono
et al.

Abstract: Pathogenic variants in ATP1A3, the α3 subunit of the Na+/K+-ATPase-encoding gene, cause alternating hemiplegia of childhood (AHC) and related disorders. Impairments in Na+/K+-ATPase activity are associated with the clinical phenotype. However, it remains unclear whether additional mechanisms are involved in the exaggerating symptoms under stressed conditions in patients with AHC. We herein report that the intracellular loop (ICL) of ATP1A3 interacted with RNA-binding proteins, such as EIF4G, PABPC1 and FMRP. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Their study also proposes a new role for CDK13 in the cytoplasm, beyond its suggested roles in transcription and RNA processing. Similarly, while investigating the role of ATP1A3 in the rare neurodevelopmental disorder alternating hemiplegia of childhood, Fujii et al (2024) uncovered that this protein interacts with key heat stress proteins to regulate protein synthesis and ensure mitochondrial stability under heat stress conditions.…”
Section: Rare Disease Research Enhances Our Understanding Of Fundamen...mentioning
confidence: 99%
“…Their study also proposes a new role for CDK13 in the cytoplasm, beyond its suggested roles in transcription and RNA processing. Similarly, while investigating the role of ATP1A3 in the rare neurodevelopmental disorder alternating hemiplegia of childhood, Fujii et al (2024) uncovered that this protein interacts with key heat stress proteins to regulate protein synthesis and ensure mitochondrial stability under heat stress conditions.…”
Section: Rare Disease Research Enhances Our Understanding Of Fundamen...mentioning
confidence: 99%